Comparison of Infrared Thermal Detection Systems for mass fever screening in a tropical healthcare setting. Issue 11 (November 2015) - Tay, M.R.; Low, Y.L.; Zhao, X.; Cook, A.R.; Lee, V.J.
Abstract: Objectives: Fever screening systems, such as Infrared Thermal Detection Systems (ITDS), have been used for rapid identification of potential cases during respiratory disease outbreaks for public health management. ITDS detect a difference between the subject and ambient temperature, making deployment in hot climates more challenging. This study, conducted in Singapore, a tropical city, evaluates the accuracy of three different ITDS for fever detection compared with traditional oral thermometry and self-reporting in a clinical setting. Study design: This study is a prospective operational evaluation conducted in the Singapore military on all personnel seeking medical care at a high-volume primary healthcare centre over a one week period in February 2014. Methods: Three ITDS, the STE Infrared Fever Screening System (IFSS), the Omnisense Sentry MKIII and the handheld Quick Shot Infrared Thermoscope HT-F03B, were evaluated. Temperature measurements were taken outside the healthcare centre, under a sheltered walkway and compared to oral temperature. Subjects were asked if they had fever. Results: There were 430 subjects screened, of whom 34 participants (7.9%) had confirmed fever, determined by oral thermometer measurement. The handheld infrared thermoscope had a very low sensitivity (29.4%), but a high specificity (96.8%). The STE ITDS had a moderate sensitivity (44.1%), but a very high specificity (99.1%). Self-reported fevers showed good sensitivity (88.2%) and specificity (93.9%). The sensitivity of the Omnisense ITDS (89.7%) was the highest among the three methods with good specificity (92.0%). Conclusion: The new generation Omnisense ITDS displayed a relatively high sensitivity and specificity for fever. Though it has a lower sensitivity, the old generation STE ITDS system showed a very high specificity. Self-reporting of fever was reliable. The handheld thermograph should not be used as a fever-screening tool under tropical conditions. Highlights: The new generation fever screening system displayed a relatively high sensitivity and specificity for fever. Self-reporting of fever was reliable compared to measured temperature. The handheld thermograph should not be used as a fever-screening tool under tropical conditions.